Biosurfactant from Lysinibacillus chungkukjangi from Rice Bran Oil Sludge and Potential Applications. Issue 5 (25th July 2016) - Bhardwaj, Garima; Cameotra, Swaranjit Singh; Chopra, Harish Kumar
Abstract: A newly discovered bacterium, Lysinibacillus chungkukjangi, was isolated from the sludge of rice bran oil processing. When the bacterium was grown on rice bran, it produced biosurfactant which reduced the surface tension of the media to 27.9 from 72 mN/m. The biosurfactant was recovered by a solvent extraction method and characterized with the help of various structure elucidation techniques viz. FTIR, 1 H‐ and 13 C‐NMR spectroscopy and LC–MS analysis. The combined results of FTIR and NMR revealed the presence of carbonyl, olefinic and aliphatic groups, with the typical spectra of lipids. Moreover, LC–MS analysis also supported the same information. The biosurfactant was also studied for its anti‐oxidant and microbial enhanced oil recovery (MEOR) potential. The anti‐oxidant activity was observed by the DPPH free radical scavenging method using ascorbic acid as the standard. The IC50 (the half maximal inhibitory concentration) was calculated and for standard, it was 0.056 mg/mL and for the biosurfactant it turned out to be 1.3 mg/mL which shows its good anti‐oxidant potential. The sandpack test was performed to check its MEOR potential and kerosene was recovered up to 90 %, which shows its excellent applicability in the MEOR processes.